The Relationship Between Physical Activity and Fiber Intake with The Incidence of Overweight in Teenagers at SMA Negeri 1 Toroh - Farizma, Kinanti Eka; Setiyaningrum, Zulia (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Overweight is a common issue among adolescents, with 9.5% of Indonesian teenagers classified as overweight in 2018. Low physical activity and inadequate fiber intake are significant contributing factors.Objective: This study aimed to analyze the relationship between physical activity and fiber intake with overweight incidence among students at SMA Negeri 1 Toroh. Methods: This descriptive quantitative study used a cross-sectional design involving 90 students from grades X, XI, and XII, selected through proportionate stratified random sampling. Physical activity was measured using a 7x24 hour activity form, fiber intake was assessed with the Sq-FFQ, and overweight status was determined based on BMI calculations. Data were analyzed using the Spearman rank correlation test. Results: Most respondents had low physical activity (81.1%) and inadequate fiber intake (88.9%). A total of 41.1% were classified as overweight. The analysis showed no significant relationship between physical activity and overweight status (p = 0.543; rs = -0.065). However, fiber intake was significantly associated with overweight status (p = 0.033; rs = 0.225).Conclusion: There is no significant association between physical activity and overweight status, but fiber intake is significantly related to overweight status among students at SMA Negeri 1 Toroh.